Reconstitution of Pure Chaperonin Hetero-Oligomer Preparations in Vitro by Temperature Modulation - Vitlin Gruber, Anna; Vugman, Milena; Azem, Abdussalam; Weiss, Celeste E. (Frontiers in Molecular Biosciences, 2018)
Chaperonins are large, essential, oligomers that facilitate protein folding in chloroplasts, mitochondria and eubacteria. Plant chloroplast chaperonins are comprised of multiple homologous subunits that exhibit unique properties. We previously characterized homogeneous, reconstituted, chloroplast-chaperonin oligomers in vitro, each composed of one of three highly homologous beta subunits from A. thaliana. In the current work, we describe alpha-type subunits from the same species and investigate their interaction with β subtypes. Neither alpha subunit was capable of forming higher-order oligomers on its own. When combined with β subunits in the presence of Mg-ATP, only the α2 subunit was able to form stable functional hetero-oligomers, which were capable of refolding denatured protein with native chloroplast co-chaperonins. Since β oligomers were able to oligomerize in the absence of α, we sought conditions under which αβ hetero-oligomers could be produced without contamination of β homo-oligomers. We found that β2 subunits are unable to oligomerize at low temperatures and used this property to obtain homogenous preparations of functional α2β2 hetero-oligomers. The results of this study highlight the importance of reaction conditions such as temperature and concentration for the reconstitution of chloroplast chaperonin oligomers in vitro.